Transforming Point Cloud data into full panoramic maps for real-time VR applications - Zang, Aldo; Carvalho, Felipe; Teixeira, Marco A; Raposo, Alberto B; Reis, Luciano P Dos (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2022: Anais do XXIV Simpósio de Realidade Virtual e Aumentada, 2022)
Nowadays the use of virtual reality (VR) and gamification to develop applications with a high degree of interactivity and realism became natural. VR applications often require the use of data captured from the real world to compose the virtual environment. This is typical in VR applications for industrial areas. One usual technique to capture the real world consists in capturing point cloud data with LIDAR scanners. However, LIDAR data demands large storage and becomes difficult to use in real time web applications. In this paper we are proposing an image-based approach in order to reduce the volume of the resulting data coming from point clouds and adapt it to a format that is easier to handle and with better performance in real time web applications.